Implementasi Sistem Monitoring pada Ikan Channa dengan Menggunakan Logika Fuzzy - Sinta Widya Ningrat, I Gusti Made; Mogi, I Komang Ari (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
Channa fish is a predatory ornamental fish that lives in fresh water, in Indonesia channa fish called snakehead fish. Channa fish or snakehead fish are widely distributed in across Asia, such as Indonesia, India, Thailand, Malaysia, and Vietnam. This fish is very much in demand nowadays. However, channa fish have problems in adapting with the water temperature and pH itself.  Imported channa fish, especially from India, are very difficult to adapt in Indonesia because of the difference the water temperature and pH. Hence Internet of Things-based system with algorithms was required to support and classify water temperature and pH data from sensors.  Fuzzy logic algorithm is a branch of mathematics which provided as problem solving modeling by computer technology. Fuzzy logic would help the channa fish to adapt in Indonesia water temperature an pH.  The result of this study was to provide a website based monitoring system to identify the value of data quality from Internet of Things sensors.